Topology optimization under design-dependent loads with the parameterized level-set method based on radial-basis functions - Jiang, Yuanteng; Zhao, Min (Computer methods in applied mechanics and engineering, 2020)
Based on the parameterized level-set method using radial basis functions, a topology optimization method is proposed that can account for design-dependent loads. First, a mathematical model of the optimization problem is established with the structural compliance minimization as the objective function and the structural volume fraction as the design constraint. By converting the line integrals into volume integrals, the design-dependent loads imposed on the structure outline described by the zero-level set are converted, and a relatively easy boundary detection method is used. Subsequently, an updating strategy of the Lagrange multiplier is proposed to make the transition of the objective function smooth during the convergence process. Finally, the effectiveness and efficiency of the proposed optimization method in solving design-dependent load problems can be shown through several classic numerical examples. •Topology optimization is applied to design-dependent loads problem.•Radial basis functions and shape derivatives are used in parameterized level set method.•A new boundary detection method is presented.•A new update strategy of Lagrange multiplier is proposed.